2015
DOI: 10.1002/2014wr016811
|View full text |Cite
|
Sign up to set email alerts
|

Climate index weighting of ensemble streamflow forecasts using a simple Bayesian approach

Abstract: Climate state can be an important predictor of future hydrologic conditions. In ensemble streamflow forecasting, where historical weather inputs or streamflow observations are used to generate the ensemble, climate index weighting is one way to represent the influence of climate state. Using a climate index, each forecast variable member of the ensemble is selectively weighted to reflect the climate state at the time of the forecast. A new approach to climate index weighting of ensemble forecasts is presented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 92 publications
1
26
0
Order By: Relevance
“…In hydrologic forecasting, Bayesian merging has been used to develop a multimodel seasonal hydrologic ensemble prediction system (Luo and Wood, 2008), to obtain probabilistic streamflow forecasts (Wang et al, 2013), or to weight the forecasts using a climate index such as the El Niño-Southern Oscillation or Pacific Decadal Oscillation (Bradley et al, 2015). However,…”
Section: Bayesian Updating (Bu)mentioning
confidence: 99%
See 2 more Smart Citations
“…In hydrologic forecasting, Bayesian merging has been used to develop a multimodel seasonal hydrologic ensemble prediction system (Luo and Wood, 2008), to obtain probabilistic streamflow forecasts (Wang et al, 2013), or to weight the forecasts using a climate index such as the El Niño-Southern Oscillation or Pacific Decadal Oscillation (Bradley et al, 2015). However,…”
Section: Bayesian Updating (Bu)mentioning
confidence: 99%
“…Assuming that the single-model forecasts are independent (Luo et al 2007), the multi-model weight * i w is the product of the eight model weights for each observation y i in the historical sample, normalized to produce a set of multi-model weights that sum to 1 (Bradley et al 2015) ( ) …”
Section: Bumentioning
confidence: 99%
See 1 more Smart Citation
“…Our ability to leverage the second source (climate predictability) depends both on how well we can characterize and predict the state of the climate and on how effectively we can incorporate this information into streamflow forecasting methods. This idea has been explored in different frameworks using standard indices, e.g., Niño3.4, the Pacific Decadal Oscillation (PDO), and/or custom (i.e., watershed-specific) climate indices derived from climate reanalyses (e.g., Grantz et al, 2005;Bradley et al, 2015), or using seasonal climate forecasts to run hydrologic model simulations (e.g., Wood et al, 2005;Yuan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One line of research has examined the potential benefits of using simulated watershed state variables -either from hydrologic or land surface modelsas predictors for statistical models (e.g., Rosenberg et al, 2011;Robertson et al, 2013). Another popular technique consists of incorporating climate information within ESP frameworks, either deriving input sequences of mean areal precipitation and temperature from current climate or climate forecast considerations (e.g., Werner et al, 2004;Wood and Lettenmaier, 2006;Luo and Wood, 2008;Gobena and Gan, 2010;Yuan et al, 2013) -referred to as pre-ESP -or ESP weighting (also referred to as post-ESP) based on climate information (e.g., Smith et al, 1992;Werner et al, 2004;Najafi et al, 2012;Bradley et al, 2015). Werner et al (2004) found that the post-ESP method (termed "trace weighting") was more effective than pre-ESP for improving forecast skill.…”
Section: Introductionmentioning
confidence: 99%